Enhancing inventory efficiency: the role of Strategic Management Accounting and Integrated Management Accounting Information systems - Lilis Puspitawati; Iqbal Lhutfi; Inomjon Qudratov (Cogent Business & Management, 2024)
This study explores how strategic management accounting (SMA) and Management Accounting Information System (MAIS) are used in inventory management and their impact on efficiency. This study involved 114 café and restaurant managers in Bandung, Indonesia as the sample. Data were analysed with PLS software, revealing that SMA and MAIS positively affect managerial efficiency. However, this study found that not all cafés and restaurants implement these systems effectively due to poor integration of SMA and MAIS indicators. This research highlights that effective use of SMA and MAIS significantly improves inventory management by providing accurate and timely information, which supports better decision-making and improves business performance. SMA is particularly useful for understanding market trends and competitors' costs, thus simplifying inventory management. This study introduces a new approach to managing stock quantities, leading to improved operational efficiency and competitive advantage. In addition, the study also emphasises the importance of risk assessment and technology in inventory management for more precise measurement and better management practices.
Keywords: G31; M15; O14; O32; 650; Inventory efficiency; strategic management accounting; integrated management accounting information systems; managerial efficiency; operational efficiency